PREVALENCE OF TOXOPLASMA GONDII IN DIFFERENT MAMMALIAN HOSTS RUSUL JASIM JAMEEL - Jameel, Rusul Jasim; alrubaie, Thakaa hassan sadiq; Altoby, Sawsan Awad Fraj; bashar, Teba majid; fadhel, Hawra'a Eyad (Journal of Medical Genetics and Clinical Biology, 2024)
Toxoplasma gondii is an obligate intracellular protozoan parasite with a global distribution across diverse mammals affecting human and animal health. This review compiles the current information on the incidences of T. gondii in various mammals; companion animals like cats and dogs, farm animals like cattle and sheep, and wild animals like deer and rodents. Research shows that it is more common in cats, the definite host in which the parasite attains sexual maturity (Dubey, 2010). It has been reported that the prevalence in livestock depends on geographical location, farming practice and environmental factors and relatively high in sheep and pigs because of their grazing and feeding behavior and direct contact with oocyst containing environment (Tenter et al. , 2000). Wildlife species remain hosts and keep the life cycle of the parasite in natural systems (Robert-Gangneux & Dardé, 2012). This compilation therefore highlights the need for constant monitoring and provision of control measures for the prevention of zoonotic transmission of T. gondii while reflecting on the various factors in host biology, the environment and human activities